Glyptothorax vatandousti, a new species of torrent catfish from the upper Karkheh drainage in Iran (Teleostei: Sisoridae) - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Freyhof, Jörg (Zootaxa, 2023)
Glyptothorax vatandousti, new species, from the upper Karkheh drainage, a tributary of the Iranian Tigris, is distinguished from its congeners in the Persian Gulf basin by having the flank with a fine, pale-brown mottled pattern overlaid by small and large, blackish or dark-brown blotches, deep caudal-peduncle (its depth 1.1–1.3 times in length), and without, or with a pale-brown triangle-shaped blotch in front of dorsal-fin origin.